2023
DOI: 10.1021/acs.est.2c09352
|View full text |Cite
|
Sign up to set email alerts
|

Potential Toxic Mechanisms of Neonicotinoid Insecticides in Rice: Inhibiting Auxin-Mediated Signal Transduction

Abstract: Inappropriate application of pesticides not only causes sub-lethal effects on ecosystem service providers but also reduces crop yield and quality. As a xenobiotic signal molecule, pesticides may interact with signal transduction receptors in crops, resulting in oxidative damage and even metabolic perturbations. We discovered that three neonicotinoid insecticides (NIs), namely, imidacloprid, thiamethoxam, and clothianidin, at 0.06–0.12 kg ai/ha significantly inhibited the auxin signal pathway in rice leaves, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…Previously found that proteins in the EPS of Bacillus subtilis were primarily adsorbed on montmorillonite surfaces via hydrogen bonds, while nucleic acids were adsorbed on goethite surfaces through ligand exchange in an acidic medium . Environmental pressures had a significant impact on microbial extracellular metabolic behavior, and the alkalinity of bauxite residue amplified this effect . Thereby, polysaccharides with abundant carboxyl functional groups were preferred by cancrinite and sodalite.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously found that proteins in the EPS of Bacillus subtilis were primarily adsorbed on montmorillonite surfaces via hydrogen bonds, while nucleic acids were adsorbed on goethite surfaces through ligand exchange in an acidic medium . Environmental pressures had a significant impact on microbial extracellular metabolic behavior, and the alkalinity of bauxite residue amplified this effect . Thereby, polysaccharides with abundant carboxyl functional groups were preferred by cancrinite and sodalite.…”
Section: Resultsmentioning
confidence: 99%
“…The protein was analyzed by using an HPLC system (Thermo Fisher Scientific ICS5000) and a CarbonPac PA20 C 18 column (3 mm × 150 mm, 10 μm). The mobile phase was NaOH/NaAc (95:5, v/v) injected at a flow rate of 0.5 mL/min, 30 °C, and detected at 230 nm …”
Section: Methodsmentioning
confidence: 99%
“…Finally, the complex with the lowest score was selected for further study. The molecular dynamics simulation protocol can be found in previous article ( Wu et al, 2023 ).…”
Section: Methodsmentioning
confidence: 99%
“…From this same perspective, Wu et al (2023) argue that neonicotinoid insecticides favor the occurrence of changes in the biosynthesis of phenylpropanoids, modifications in genes that encode peroxidases, culminating in oxidative stress and a decrease in antioxidant metabolites. Concerning the comparison between storage periods, for the "Peroxidase protein" and "Peroxidase activity" variables, there were significant differences between them (p-value < 0.05).…”
Section: Peroxidase Activitymentioning
confidence: 99%